EGFR exon 20 insertion variants A763_Y764insFQEA and D770delinsGY confer favorable sensitivity to currently approved EGFR-specific tyrosine kinase inhibitors - Yang, Guangjian; Yang, Yaning; Hu, Jiaqi; Xu, Haiyan; Zhang, Shuyang; Wang, Yan (Frontiers in Pharmacology, 2022)
Background: The EGFR exon 20 insertions (ex20ins) D770_N771insSVD and V769_D770insASV are most frequent in non-small cell lung cancer (NSCLC), and are associated with intrinsic resistance to currently approved EGFR tyrosine kinase inhibitors (TKIs). A763_Y764insFQEA and D770delinsGY respectively account for 3%-8% and 2.0%-4.8% of EGFR ex20ins in NSCLC, and are associated with a more favorable response to EGFR-specific TKIs as per case reports. The aim of this study was to elucidate the molecular structures of these mutants and their binding affinities to diverse EGFR TKIs, and compare the clinical outcomes in NSCLC patients harboring these mutations. Methods: A real-world cohort study was conducted to evaluate and compare the clinical outcomes of EGFR TKIs among NSCLC patients with different EGFR ex20ins mutants in response to EGFR TKIs. The structures of A763_Y764insFQEA and D770delinsGY were also analyzed and drug binding simulations were performed. Results: With a median follow-up of 24.0 months, the first-line objective response rate (ORR), disease control rate (DCR), and median progression-free survival (PFS) were respectively 0 (0/16), 50.0% (8/16), and 2.07 months (95%CI, 0-6.25) in patients harboring D770_N771insSVD and V769_D770insASV variants, and 33.3% (4/12), 83.3% (10/12), and 9.97 months (95%CI, 4.75-15.19) in patients with A763_Y764insFQEA and D770delinsGY variants. There was a significant difference between the PFS of these two subgroups (median, 9.97 vs.2.07 months, HR=0.33, 95%CI, 0.13-0.85, P=0.02). Similarly, the PFS was significantly longer after second-line treatment with EGFR TKIs in patients harboring A763_Y764insFQEA and D770delinsGY compared to those with other insertions (median, 6.77 vs.2.23 months, HR=0.14, P<0.001). Computational simulations indicated that A763_Y764insFQEA and D770delinsGY mutants were structurally similar to wild type EGFR. In contrast, the C-helix and phosphate-binding loop of D770_N771insSVD and V769_D770insASV had shifted into the drug-binding pocket, resulting in significant steric hindrance and a lack of affinity for the currently approved EGFR inhibitors. Conclusion: NSCLC patients harboring A763_Y764insFQEA and D770delinsGY insertions of EGFR are responsive to the currently approved EGFR TKIs as opposed to patients with the D770_N771insSVD and V769_D770insASV variants. Therefore, A763_Y764insFQEA and D770delinsGY should be classified as active mutations among heterogeneous EGFR ex20ins subtypes and the carriers can be treated with the suitable EGFR TKIs.